Double Helix Phenomenology on Digital Adaptive Leadership and Innovation Management’s Practice-Perspective During Pandemic - Hutasoit, Ridhony Marisson Hasudungan (Interdisciplinary Social Studies, 2023)
ackground: The Financial Services Sector significantly impacts Indonesia’s economic growth and resilience. The COVID-19 Pandemic has significantly affected the financial services sector. Therefore, the Inodesia Financial Services Authority (OJK), as the regulator of the financial services sector, needs to respond appropriately to the impact of the pandemic. The OJK established based on Law Number 21 of 2011, has the authorities, OJK has regional representative offices. One of them is OJK Southeast Sulawesi Province (OJK Sultra). Aim: Analize OJK Sultra’s efforts to achieve performance in facing the challenges of the pandemic are a form of implementing digital adaptive leadership and innovation management which have become phenomena that has been elaborated through 19 informants and 10 internal documents. Method: The phenomenological methodology is the researcher’s choice in elaborating on the practices and perspectives of the two phenomena in question. The researcher modifies the phenomenological methodology by combining historical concepts (experience) and hermeneutics with a period set at the researcher’s beginning, called Historical-Hermeneutic Phenomenology (Double Helix Phenomenology). This modified methodology also has an impact on the analytical technique that needs to be modified by combining the Colaizzi model data analysis with the technical analysis of Interpretative Phenomenological Analysis (IPA) into a Historical-Phenomenological Interpretation Analysis or Historic-Interpretative Phenomenological Analysis (H-IPA). Findings: The research findings found eight elements for digital adaptive leadership and six elements for innovation management to achieve work unit performance during the pandemic successfully.